Male gamblers – suicide victims and living controls: comparison of adversity over the life course. Issue 1 (2nd January 2016) - Andronicos, Mélina; Beauchamp, Guy; Robert, Marie; Besson, Jacques; Séguin, Monique
Abstract: The objective of this research is to investigate the possible difference in accumulation of adversity over the life course among decedent gamblers and living control gamblers in the province of Quebec, Canada. A sample of 90 adult men, 41 living participants and 49 suicide decedents, met the criteria for at-risk and problem gambling over the last five years. Data were obtained from informants in the case of suicide and directly from living controls during semi-structured face-to-face interviews using SCID I and II, SOGS, Module K and a recount of life trajectories methodology. The results showed a high level of adversity throughout the life trajectories of both groups. However, the living gamblers faced more difficulties during their lifespan than the suicide victims. In the last six months before their death, suicide victims had a significantly higher number of mental health disorders, especially co-morbid mental health disorders and anxiety, compared to the living controls. We also observed a rapid escalation of difficulties, more life events and more psychological distress in the last six months of their lives among the suicide decedents. Suicidal behaviour needs to be carefully investigated by medical staff and mental health practitioners, especially when gamblers demonstrate evidence of mental health disorders or financial difficulties.